Illusions of Innocence Protestant Primitivism in America, 1630-1875 - Hughes, Richard T. (Abilene Christian University Press, 1988)
History helps us understand who we are and what we should become. This book demonstrates that primitivism is central to American religion. Primitivism is the dream of restoring religion to a purer order, as found in former times.